2019
DOI: 10.1177/1557988319849734
|View full text |Cite
|
Sign up to set email alerts
|

Invisibility Is Not Invincibility: The Impact of Intimate Partner Violence on Gay, Bisexual, and Straight Men’s Mental Health

Abstract: Intimate partner violence (IPV) is a critical public health problem. However, there is limited research conducted on and about men who are survivors. This project extends previous research by examining the post-traumatic impact of diverse forms of IPV (sexual, physical, emotional, control, and stalking) on the internalized and externalized mental health of gay, bisexual, and straight men. Using data from the National Intimate Partner and Sexual Violence Survey (2011; N = 18,957), we find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 66 publications
0
18
0
2
Order By: Relevance
“…Studies largely recruit heterosexual samples and seldom take stock of sexual minority populations (Chen et al, 2020; Langenderfer-Magruder et al, 2020; Sheridan et al, 2019; Strand & McEwan, 2011), resulting in a scarcity of empirical data in the stalking literature base to expand the issue to gay and bisexual men (Black et al, 2011; Pathé et al, 2000). While many IPV studies exclude experiences of stalking, one study that examined both phenomena indicated that 66.27% of gay men and 60.38% of bisexual men reported victimization of intimate stalking as a form of IPV ( N =136; Dickerson-Amaya & Coston, 2019). This compares with 26% of gay men and 37% of bisexual men who have experienced IPV that covers a range of abusive experiences (Breiding et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies largely recruit heterosexual samples and seldom take stock of sexual minority populations (Chen et al, 2020; Langenderfer-Magruder et al, 2020; Sheridan et al, 2019; Strand & McEwan, 2011), resulting in a scarcity of empirical data in the stalking literature base to expand the issue to gay and bisexual men (Black et al, 2011; Pathé et al, 2000). While many IPV studies exclude experiences of stalking, one study that examined both phenomena indicated that 66.27% of gay men and 60.38% of bisexual men reported victimization of intimate stalking as a form of IPV ( N =136; Dickerson-Amaya & Coston, 2019). This compares with 26% of gay men and 37% of bisexual men who have experienced IPV that covers a range of abusive experiences (Breiding et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Compared with heterosexual men and women, gay and bisexual men have been found to experience IPV five times more than heterosexual men (Yu et al, 2013). Dickerson-Amaya and Coston’s (2019) study included bisexual, gay, and heterosexual men and reported victimization prevalence rates of IPV as 79%, 83%, and 62%, respectively, for these three cohorts, highlighting the added vulnerability of gay and bisexual men to IPV. Several studies have documented that gay and bisexual men experience rates of violence equivalent to or higher than heterosexual women (Finneran & Stephenson, 2013, 2014a; Frierson, 2014; Goldenberg et al, 2016; Houston & McKirnan, 2007; Kay & Jeffries, 2010; Pimentel, 2015; Rollè et al, 2018; Woodyatt & Stephenson, 2016).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Even though many of those men who experienced interpersonal violence suffer negative physical or mental health consequences [ 8 10 ], men are in general reluctant to seek formal or medical help after experiencing violence [ 11 13 ]. The Model of Pathways to Treatment [ 14 , 15 ] explains people’s help-seeking behavior.…”
Section: Backgroudmentioning
confidence: 99%